BUILDING THE COMPETITIVENESS OF EDUCATION BASED ON PEDAGOGIC COMPETENCE - Madhakomala Madhakomala; Riyani Putriardi; Widad Diana (PT. BATARI EDU CALYA, 2023)
This paper describes a conceptual proposal for building educational competitiveness based on pedagogic competence. It is undeniable that the role of education in advancing the life of society and the nation has a very vital role. A good educational system and activity will determine the quality of the nation and society, both locally and globally. Therefore, a conceptual construction is needed in an effort to build educational competitiveness. Through a qualitative approach, descriptive analysis method with literature study as a data collection tool. The collected data is then analyzed descriptively to be presented comprehensively. From the results of the study, it was found that a teacher or educator needs to have pedagogical competence that can be the basis for producing quality graduates. The pedagogic competence mastered by an educator provides a direction to improve the quality of education. The principles of relevance, flexibility, and continuity, provides a foundation for increasing competitiveness in the world of education